2017
DOI: 10.1055/s-0036-1589062
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium-Catalyzed Alkyne Carbo- and Cycloalumination Reactions in Stereoselective Preparation of 1-Alkenyl Selenides

Abstract: Supporting informationThe reagents were obtained from Sigma-Aldrich or Acros. Dichloromethane and hexane were distilled over P 2 O 5 . Organic diselenides were prepared by the reaction of elemental selenium with hydrazine hydrate and bromobenzene or bromoalkane under the action of sodium hydroxide solution in DMF [1]. The alkynyl selenides were prepared by the reaction of terminal alkynes with elemental selenium and bromoalkanes [2]. IR spectra were recorded on Bruker VE Vertex 70v spectrometer as liquid films… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In order to further study transformations of acetylenic compounds under the organoniobium synthesis conditions, we made attempts to develop efficient reagents for transformations of niobiacyclopropene intermediates. Previously, we have demonstrated that sulfonic acid derivatives, such as sulfonyl halides, sulfonic acid silyl esters, alkylthiosulfonates, organic disulfides and diselenides are efficient electrophilic reagents for the functionalization of organoaluminum compounds, such as 1-alkenylalanes, which can be used to prepare the corresponding alkenyl halides [ 57 ], alkenylsilanes [ 58 ], alkenyl sulphides [ 59 , 60 ] and alkenyl selenides [ 61 ] in high yields under mild conditions. We expected that sulfonyl halides would also be reactive toward niobiacyclopropene intermediate generated in this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In order to further study transformations of acetylenic compounds under the organoniobium synthesis conditions, we made attempts to develop efficient reagents for transformations of niobiacyclopropene intermediates. Previously, we have demonstrated that sulfonic acid derivatives, such as sulfonyl halides, sulfonic acid silyl esters, alkylthiosulfonates, organic disulfides and diselenides are efficient electrophilic reagents for the functionalization of organoaluminum compounds, such as 1-alkenylalanes, which can be used to prepare the corresponding alkenyl halides [ 57 ], alkenylsilanes [ 58 ], alkenyl sulphides [ 59 , 60 ] and alkenyl selenides [ 61 ] in high yields under mild conditions. We expected that sulfonyl halides would also be reactive toward niobiacyclopropene intermediate generated in this reaction.…”
Section: Resultsmentioning
confidence: 99%
“… [237] Following the hydrometallation of alkynes, a methylalumination of terminal and internal alkynes was reported to synthesize vinyl selenides 171 (Scheme 163). [238] The methylalumination leads to the initial formation of an alkenylalanes intermediate I , which reacts with diorganyl diselenides to give the product.…”
Section: Diorganyl Diselenides Promoting Reduction Of Alkynesmentioning
confidence: 99%
“…Most general and efficient methods described for the preparation of vinyl selenides involves hydroselenation of alkynes, hydrometallation of alkynyl selenides, halogenation of alkynyl selenides, transition metal‐catalyzed diorganyl diselenides additions to alkynes, Horner, Wittig olefination, condensation reactions, selenium electrophilic addition to alkynes and selenium‐radical addition to alkynes . However, these very important methodologies require the use of metal transition, the previous preparation of diorganyl diselenides or very unstable selenols and the use of harsh reaction conditions, delivering serious limitations.…”
Section: Introductionmentioning
confidence: 99%